STRUCTURAL ORGANIZATION OF TRACHEA AND PRIMARY BRONCHUS OF THE 7-10 MONTHS’ FETUS - Khmara, Т.V.; Fedoniuk, L.Ya.; Sarafiniuk, L.А.; Halahdyna, А.А.; Honcharenko, V.А. (World of Medicine and Biology, 2019)
The histological examination was conducted on 24 series of the thoracic part histological sections of trachea and the primary bronchus in the human fetus of 231.0-375.0 mm of parietal-coccyхal length. Microscopic study of the trachea and bronchus in the fetus of 231.0-375.0 mm TKD showed that their wall consists of mucosa, submucosa, fibrous-cartilage layer and adventitia, which in different age periods have their structural features. Histological examination of the trachea and primary bronchus in the early period of the ontogenesis of the human fetus revealed a fragmentary nature of the cartilage skeleton structure of the trachea and primary bronchus at the completion of the formation of other layers. It was established that at the end of the fetal period of ontogenesis (311.0-375.0 mm PCL), an intensive development of the components of the trachea wall and primary bronchus, which anatomically causes increased growth and formation in this period of prenatal ontogenesis, is observed.
Keywords: trachea; primary bronchus; microscopic structure; fetus; human